Mucuna pruriens seed extract promotes neurite outgrowth via Ten-4 dependent and independent mechanisms in neuro2a cells - Sutin Wansawat; Mani Iyer Prasanth; Isidoro, Ciro; Tewin Tencomnao (Penerbit Universiti Kebangsaan Malaysia, 2018)
Neurological diseases are one of the serious health hazards faced by mankind for decades. Neurite outgrowth is a key factor responsible for proper neuronal development. Any misplacement in the process could lead to neurological diseases like Alzheimer’s and Parkinson’s. Treatment with the available synthetic drugs imparts many difficulties to the patients due to the side effects. Compounds from natural sources can be considered as an effective replacement for this. Mucuna pruriens, used in traditional ayurvedic medicine, contains L-3,4-dihydroxy phenylalanine (L-DOPA) in its seeds, which possesses medicinal effects against neurological diseases. In this regard, seed extracts of M. pruriens originated from Thailand and India, were analyzed for their neuroprotective effects in Neuro2a cells. Hexane, ethyl acetate and ethanol extracts were found to be non-toxic to the viability of the cells. Ethanol extracts of M. pruriens of Thai origin (MTE), hexane extracts of M. pruriens of Indian origin (MIH) and ethyl acetate extracts of M. pruriens of Indian origin (MIEA) were able to induce neurite outgrowth in Neuro2a cells. Interestingly, both MTE and MIH induced neurite outgrowth dependent on Teneurin-4 (Ten-4) transmembrane protein whereas MIEA did the same independent of Ten-4, which was confirmed by real time PCR and gene silencing approach. The present study suggested that M. pruriens can be used as a potential drug in the treatment of neurological diseases as it can induce neurite outgrowth by multiple mechanisms, which will be of great use in the field of medicine.